Multifunctional nanolayered renewable carbon for electromagnetic interference and energy devices. (June 2021) - Semeniuk, M.; Tandon, R.; Gauvin, R.; Tjong, J.; Jaffer, S.; Lu, Z.-H.; Sain, M.
Abstract: Controlled carbonization of biomass leads to nanolayered graphitic structures with characteristic crystalline sp 2 hybridization, conductive properties up to 600 S/m, and electromagnetic interference shielding effectiveness of 47.7 dB at 12 GHz. We investigate functional properties of nanolayered renewable carbon, including conductive and photoluminescent features, leading to a new understanding of structure–property correlation and their graphitic multilayered nanostructures. Some unique and novel behaviors, such as negative dielectric factors, hold promise in the areas of cofactor sensors and electromagnetic interference shielding due to their correlation with the absorption of microwave radiation. An electromagnetic interference device demonstrates an application of these nanographitic carbon materials. These conductive and photoluminescent carbon materials hold significant promise in applications such as power electronics, batteries, and sensors, where they may replace conventional metal and graphene. Graphical abstract: Image 1 Highlights: Novel nanolayered graphitic structure highly conductive and photoluminescent. An EMI shielding device with effectiveness of 47.7 dB and conductivity of 600 S/m. Negative dielectric factors with potential for microwave radiation absorption. Graphene layered structure derived from entirely natural sources. Carbonized biomass to block satellite broadcasting signals.